The Effect of Leadership Style and Work Stress on Employee Performance at Efarina University Pematangsiantar - Ginting, Yesenia Anastasiar Br.; Nainggolan, Yenni Martha; Panjaitan, Santi Rohdearni; Panjaitan, Hadi; Nainggolan, Anju Bherna D (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This research was conducted at Efarina University, Pematangsiantar. The purpose of this study was to determine the effect of leadership style and work stress on Efarina University employees, both partially and simultaneously. The population in this study were all Efarina University employees totaling 50 employees and the sample used in this study was 50 people. The method of determining the sample in this study was using the saturated sampling method (census). The data used were primary data and secondary data. The data analysis method used was the descriptive analysis method and the quantitative analysis method. The results showed that leadership style positively influenced the performance of Efarina University employees. Work stress positively influenced the performance of Efarina University employees. In a simultaneous test, leadership style and work stress had an influence on the performance of Efarina University employees. The magnitude of the influence of leadership style and work stress on the performance of Efarina University employees was 63.9% while the remaining 36.1% was influenced by other variables not examined in this study.